The Regulatory Subunit of Protein Kinase A (Bcy1) in Candida albicans Plays Critical Roles in Filamentation and White-Opaque Switching but Is Not Essential for Cell Growth - Ding, Xuefen; Cao, Chengjun; Zheng, Qiushi; Huang, Guanghua (Frontiers in Microbiology, 2017)
The conserved cAMP-dependent protein kinase (PKA) is composed of the regulatory and catalytic subunits and acts as the central component of the cAMP signaling pathway. In the human fungal pathogen Candida albicans, the PKA regulatory subunit Bcy1 plays a critical role in the regulation of cell differentiation and death. It has long been considered that Bcy1 is essential for cell viability in C. albicans. In the current study, surprisingly, we found that Bcy1 is not required for cell growth, and we successfully generated a bcy1/bcy1 null mutant in C. albicans. Deletion of BCY1 leads to multiple cellular morphologies and promotes the development of filaments. Filamentous and smooth colonies are two typical morphological types of the bcy1/bcy1 mutant, which can undergo spontaneous switching between the two types. Cells of filamentous colonies grow better on a number of different culture media and have a higher survival rate than cells of smooth colonies. In addition, deletion of BCY1 significantly increased the frequency of white-to-opaque switching on N-acetylglucosamine (GlcNAc)-containing medium. The bcy1/bcy1 null mutant generated herein provides the field a new resource to study the biological functions of the cAMP signaling pathway in C. albicans.